Easier Said Than Done: Gender differences in Perceived Barriers to Gaining a Mentor - Ragins, Belle Rose; Cotton, John L. (Academy of Management Journal, 1991)
This study examined factors related to perceived barriers to gaining a mentor. Women reported more such barriers than men. In addition, individuals lacking previous experience as proégés reported greater barriers to obtaining a mentor than experienced protégés. Theoretical implications are discussed.